2003
DOI: 10.1021/ie020839i
|View full text |Cite
|
Sign up to set email alerts
|

Practical Modeling of Metal Hydride Hydrogen Storage Systems

Abstract: A new approach is introduced to model the discharge behavior of a metal hydride hydrogen storage bed. The reversible reaction kinetics and the empirical van't Hoff relationship used in a typical reactor model are replaced by a solid-phase diffusion equation and a semiempirical equilibrium P−C−T relationship. Two new semiempirical P−C−T models are also introduced based on modified virial and composite Langmuir expressions. By varying the heat- and mass-transfer coefficients, the model was calibrated to experime… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2005
2005
2020
2020

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 27 publications
(6 citation statements)
references
References 21 publications
0
6
0
Order By: Relevance
“…The use of fins, foams, meshes and matrices formed by high conductivity materials like Cu, Al, Fe and Ni have been reported (Oi et al, 2004;Gadre et al, 2003), and the use of expanded graphite/metal-hydride compacts were shown to increase the conductivity from 0.1 to 3 W m À1 K À1 (Klein and Groll, 2004) with only a 2.1 wt% graphite additive. This opens up the possibility of designing functional nanocomposites, where an external matrix could play the double role of increasing the heat transfer while being chemically active in promoting desirable thermodynamic and kinetic properties of the hydride.…”
Section: Functional Matrices and Nanocompositesmentioning
confidence: 99%
“…The use of fins, foams, meshes and matrices formed by high conductivity materials like Cu, Al, Fe and Ni have been reported (Oi et al, 2004;Gadre et al, 2003), and the use of expanded graphite/metal-hydride compacts were shown to increase the conductivity from 0.1 to 3 W m À1 K À1 (Klein and Groll, 2004) with only a 2.1 wt% graphite additive. This opens up the possibility of designing functional nanocomposites, where an external matrix could play the double role of increasing the heat transfer while being chemically active in promoting desirable thermodynamic and kinetic properties of the hydride.…”
Section: Functional Matrices and Nanocompositesmentioning
confidence: 99%
“…5 1, then u y = O(Re −0.5 ), ∂/∂y = O(Re 0.5 ), and the viscous terms are O(Re −1 ). One can define the flow shear, heating, and averages of a generic variable Ψ that may be ρ, u r , ρu r , and ρu 2 r as…”
Section: Lateral Flowmentioning
confidence: 99%
“…Although storage by absorption or adsorption does not usually happen at high pressures, possible tank heating by fire can result in high-pressure release. For example, Anton et al [4] and Gadre et al [5] find that for the case of metal hydride storage, the relevant phase equilibrium equations can give pressures of O(10 2 bar) at temperatures in the range 400-500 K. While low-pressure GH2 release is possible for the last two mentioned storage types, this would inherently result in minimal hazard, or one that overlaps with the slow release scenario described below.…”
Section: Introductionmentioning
confidence: 99%
“…A numerical model that calculated the pressure and temperature histories associated with H 2 desorption from a lanthanum-rich mischmetal (Lm) hydride bed alloyed with nickel and aluminum, Lm 1.06 Ni 4.96 Al 0.04 , was developed by Gadre, Ebner, Al-Muhtaseb and J. Ritter [2003]. The models were able to predict the P-T behavior of the hydride bed at low discharge rates.…”
Section: Literature Reviewmentioning
confidence: 99%